2022
DOI: 10.3390/biomedicines10020243
|View full text |Cite
|
Sign up to set email alerts
|

The Expanded Endocannabinoid System Contributes to Metabolic and Body Mass Shifts in First-Episode Schizophrenia: A 5-Year Follow-Up Study

Abstract: Alterations in the expanded endocannabinoid system (eECS) and cell membrane composition have been implicated in the pathophysiology of schizophrenia spectrum disorders. We enrolled 54 antipsychotic (AP)-naïve first-episode psychosis (FEP) patients and 58 controls and applied a targeted metabolomics approach followed by multivariate data analysis to investigate the profile changes in the serum levels of endocannabinoids: 2-arachidonoylglycerol (2-AG) and anandamide, endocannabinoids-like N-acylethanolamines (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…These alterations appeared against the background of persistent BMI and waist circumference increases in the sample of patients. Meta-analyses [ 1 , 43 ] and our previous studies [ 31 , 32 ] have convincingly shown that patients with a chronic psychotic disorder have an increased risk of abdominal obesity, diabetes and MetS when compared with cohort-matched general population controls. It has been suggested that waist circumference appears to capture a major part of the health risks related to the amount of body fat [ 44 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These alterations appeared against the background of persistent BMI and waist circumference increases in the sample of patients. Meta-analyses [ 1 , 43 ] and our previous studies [ 31 , 32 ] have convincingly shown that patients with a chronic psychotic disorder have an increased risk of abdominal obesity, diabetes and MetS when compared with cohort-matched general population controls. It has been suggested that waist circumference appears to capture a major part of the health risks related to the amount of body fat [ 44 ].…”
Section: Discussionmentioning
confidence: 97%
“…The same FEP and CSs groups were partially characterized in our previous studies [ 7 , 8 , 30 ], wherein we focused on describing the inflammatory biomarkers and metabolomic profiles in AP-naïve FEPs ( n = 38) compared to controls ( n = 37) and demonstrated changes in biomolecule profiles over 0.6 years. To describe even longer-term changes due to disease and treatment, we then increased the total number of subjects in the study, also collected patient data at 5.1 years after initiation of AP therapy, and described changes in amino acid, biogenic amine profiles and endocannabinoids in the FEP group, before initiating AP therapy, as well as over 0.6- and 5.1-year periods [ 31 , 32 ]. At present, 5.1-year longitudinal data from 54 patients and data from 58 controls (partially the same cohort as described previously) were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Unbiased lipidomic profiling with LC-MS/MS is conventionally measured using data-dependent acquisition, a lipid screening format that biases abundant lipids. Targeted screening methods, such as MRM, aid the identification of lipids of interest, down to picomolar concentrations, and were employed to identify eCBs and eicosanoid disruptions in SSD etiology ( 51 , 52 , 62 , 69 , 74 , 75 ). Data-independent acquisition is an alternative global lipidomic approach, providing a more diverse lipidomics profile.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Parksepp et al . ( 75 ) conveyed a direct and dynamic influence of membrane phospholipids on ECS regulation in SSD. In their 5-year investigation, levels of peripheral ECS regulators and NAEs were examined along with their phospholipid precursors.…”
Section: Lipidomics Investigations Into Ssd and Psychosis Fluid Bioma...mentioning
confidence: 99%
See 1 more Smart Citation